Roles of curcumin in preventing pathogenesis of Alzheimer's disease - Wasana Pratchayasaku (2018)
Curcumin is a yellow-orange powder derived from the rhizome of Curcuma longa Linn. In traditional medicine, curcumin has been used to treat several diseases. Much evidence has shown curcumin's anti-ulcer, anti-cancer, anti-hepatotoxic, anti-viral, accelerated wound healing, cardioprotective, hypoglycemic and anti-inflammatory properties. Recently, several in vitro and in vivo studies have shown that curcumin has various properties which help prevent the pathogenesis of Alzheimer's disease (AD). These effects include anti-amyloid, anti-inflammation, antioxidant, anti-apoptotic and cholesterol lowering properties. These findings suggest the possible benefits of curcumin in AD therapy. In this review, the pathogenesis of, as well as current therapeutic strategies for, AD are presented and evidence of the role of curcumin in preventing the pathogenetic cascades which underlie AD are discussed. Copyright © 2009 by New Century Health Publishers, LLC.